STRATEGI PENGEMBANGAN KAWASAN AGROPOLITAN BELAJEN KECAMATAN ALLA KABUPATEN ENREKANG - -, Rosida (Jurnal Ilmiah Ecosystem, 2016)
This study aims to formulate development strategies Agropolitan Belajen District of Alla Enrekang based on potentials and constraints that exist in the region and to know how big contribution of the agricultural sector to the GDP Enrekang. Data were collected using direct survey approach, visualization of the object under study and conduct institutional survey on institutions associated with the data and information needed.The results showed that (1) the development strategy of the agropolitan Belajen District of Alla Enrekang is to create synergies region harmonious and sustainable and to create linkages and interactions between regions (2), contribution of agriculture to the GDP Enrekang amounted to nine point thirteen percent, wherein the component sector is growing district that has a positive value was mining and quarrying, manufacturing, electricity, gas and water supply, construction, trade, hotels and restaurants, transport and communications as well as financial, leasing and business services.